2015
DOI: 10.1021/jacs.5b07908
|View full text |Cite
|
Sign up to set email alerts
|

Modular and Chemically Responsive Oligonucleotide “Bonds” in Nanoparticle Superlattices

Abstract: Chemical bonds are a key determinant of the structure and properties of a material. Thus, rationally designing arbitrary materials requires complete control over the bond. While atomic bonding is dictated by the identity of the atoms, nanoparticle superlattice engineering, where nano-particle “atoms” are held together by DNA “bonds”, offers a route to design crystal lattices in a way that nature cannot: through altering the oligonucleotide bond. Herein, the use of RNA, as opposed to DNA, is explored by synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Since results from gold-based SNAs indicated that degradation of surface-displayed RNA by serum nucleases can occur rapidly in certain sequence contexts, 22,39,40 we also synthesized 2 ′ F-RPA-NPs that incorporate 2′-fluoropyrimi-dines within the RNA sequence. This sugar modification has proven useful in mediating nuclease resistance and reducing immunogenicity while maintaining efficacy of siRNAs.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Since results from gold-based SNAs indicated that degradation of surface-displayed RNA by serum nucleases can occur rapidly in certain sequence contexts, 22,39,40 we also synthesized 2 ′ F-RPA-NPs that incorporate 2′-fluoropyrimi-dines within the RNA sequence. This sugar modification has proven useful in mediating nuclease resistance and reducing immunogenicity while maintaining efficacy of siRNAs.…”
Section: ■ Resultsmentioning
confidence: 99%
“…applications. For colloidal crystals in general, notable applications include photonics 4,5 , sensing 6,7 , and catalysis 8,9 . By controlling the relative sizes of colloidal particles in binary systems and the nature of their interactions, a myriad of structures have been produced experimentally from self-assembly: CsCl, NaCl, CuAu, NaTl, AlB 2 , MgZn 2 , Cr 3 Si, Cu 3 Au, Cs 6 C 60 , and others 2,3,[10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…If these results were extended to lower-symmetry particles (e.g., tetrahedra), one would imagine an even smaller zone of anisotropy and richer phase diagram, including the possibility of quasicrystal or diamond lattices (20,30,36,39). Due to the highly modular and programmable nature of nucleic acids, the location of these phase transitions can likely be tuned depending on the desired structure, via modulation of the design (e.g., flexibility) (40) or the type of nucleic acid used (e.g., locked nucleic acid or RNA) (41). Beyond defining the zone of anisotropy, this work also establishes a strategy to assemble nonspherical building blocks into a rich set of different phases based on the interplay of the particle and ligand structure.…”
mentioning
confidence: 99%